Comparative analysis of bile metabolic profile in patients with biliary obstruction complicated by Clonorchis sinensis infection - Zhang, Xueli; Han, Su; Jiang, Xu; Duan, Shanshan; Gao, Yannan; Ding, Jian; Li, Xiang; Sun, Beibei; Hu, Xinyi; Zhang, Xiaoli; Zhang, Weizhe (Frontiers in Cellular and Infection Microbiology, 2023)
Background Clonorchiasis is an important foodborne parasitic disease. However, eggs of Clonorchis sinensis (C. sinensis) cannot be detected in feces during biliary obstruction. Moreover, many diseases can cause biliary obstruction, such as gallstones, adenocarcinoma, cholangiocarcinoma and Ascaris lumbricoides infection. Therefore, it is of great significance to distinguish between patients of biliary obstruction and biliary obstruction with C. sinensis infection. Methods A total of 48 biliary obstruction patients were enrolled, including 23 infected with C. sinensis (C. sinensis) (OB+C.s) and 25 non-infected subjects (OB). The bile samples were collected by endoscopic retrograde cholangiopancreatography and analyzed using ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-QTOF MS). Additionally, multivariate statistical analysis methods were employed to identify differential metabolites. Next, bile amino acid levels were determined by targeted metabolomics analysis. Result A total of 146 and 132 significant metabolites were identified in electrospray ionization (ESI)+ and ESI− modes, respectively. The levels of amino acids (asparagine, glutamate, ornithine) and polyamines (spermidine and spermine) were significantly changed. Targeted analysis showed that the levels of amino acids (such as L-arginine, L-glutamine, L-lysine, L-propionic, and L-tyrosine) were lower in OB+C.s patients compared to those in OB patients. Marked metabolic pathways were involved in “Glutathione metabolism”, “Caffeine metabolism”, “Alanine, aspartate and glutamate metabolism”, “Arginine and proline metabolism”, “Purine metabolism”, “Beta-Alanine metabolism”, and “D-glutamine and D-glutamate metabolism”. Conclusion These results show that there were significant differences between OB+C.s and OB patients, especially in amino acids. The metabolic signature and perturbations in metabolic pathways may help to better distinguish OB+C.s and OB patients.